Relativistic R-matrix calculations of the photoionization of W63+ ions. (2nd April 2021) - An, Y H; Wu, Z W; Jiang, J; Xie, L Y; Zhang, D H; Dong, C Z
Abstract: The direct and resonant single-photon photoionization of W 63+ ions from their ground state 1 s 2 2 s 2 2 p 6 3 s 2 S 1/2 and four lowly-excited states 1 s 2 2 s 2 2 p 6 3 p 2 P 1/2, 3/2 and 1 s 2 2 s 2 2 p 6 3 d 2 D 3/2, 5/2 has been studied within the framework of the relativistic R-matrix method and the multiconfigurational Dirac–Fock method. Special attention has been paid to obtaining direct and resonant ionization limits and to identifying possible resonant symmetries of W 63+ ions. To this end, the photoionization cross-sections have been calculated using the Dirac Atomic R-matrix Code package. Direct and resonant ionization limits were obtained for the ground-state photoionization of W 63+ ions, and the resonant peaks identified were found to be associated with the resonances 1 s 2 2 s 2 2 p 5 3 lnl ′ and 1 s 2 2 s 2 p 6 3 lnl ′ ( l, l ′ = s, p, d ) for the fine-structured energy level or configuration at the level of fine structure or configuration. For excited-state photoionization, however, the resonant ionization limits and resonant peaks were hardly distinguishable due to much more densely spaced resonant peaks and a complicated resonant structure, although the respective direct ionization limits are obtained. We expect that this work will remedy the current lack of fundamental studies of the photoionization of W 63+ ions and be helpful in the diagnosis and simulation of fusion plasmas in conjunction with the available photoionization data for tungsten ions in other charge states.